1107. The MAAGE Study: Health Care Utilization for the Treatment of Medically Attended Acute Gastroenteritis. (26th November 2018) - Mattison, Claire P; Groom, Holly; Donald, Judy; Salas, S Bianca; Marsh, Zachary; Burke, Rachel M; Schmidt, Mark A; Hall, Aron J; Naleway, Allison L
Abstract: Background: Acute gastroenteritis (AGE) exacts a substantial disease burden across the age spectrum, although healthcare utilization for AGE is not well characterized. Through active surveillance of medically attended acute gastroenteritis (MAAGE) encounters within a large, integrated healthcare delivery system, we analyzed demographic patterns of healthcare utilization among AGE patients. Methods: From April 1, 2014 to September 30, 2016, we collected information on all MAAGE encounters in Kaiser Permanente Northwest (KPNW) patients through daily abstraction from electronic health records using ICD-9/-10 codes. For each patient, a MAAGE episode was defined as all MAAGE encounters <30 days apart. Results: There were 109, 493 MAAGE encounters among 39, 451 patients. Patients were 60.4% female and 39.6% male; 10.3% were <5 years old, 9.7% were 5–17, 31.1% were 18–44, 25.4% were 45–64, and 23.5% were ≥65. Among those with known race, 87.2% were white; 4.1% were Asian, 3.6% were black, and 5.1% were other or multiple races. Prevalence of any chronic comorbid condition was 52.9%. Of 52, 107 MAAGE episodes, 81.0% first presented as outpatients; this was most common in those aged <5 (92.1%) and decreased with age to 75.0% in those ≥65. First presenting remotely (email or telephone) ranged from 4.0% in those aged <5 to 19.3% in those ≥65; 52.7% of episodes first presenting remotely had no subsequent visits. Few episodes first presented to an emergency department (3.8% in <5 year olds to 6.6% in 18–44 year olds) or inpatient setting (0.1% in <5 year olds to 1.7% in ≥65 year olds). Most MAAGE episodes comprised of one encounter (median: 1.0, mean: 2.1). The number of encounters per episode was lowest in those <5 years old (median: 1.0, mean: 1.5) and highest in those ≥65 (median: 2.0, mean: 2.5). Most deaths within 30 days from the start of an episode (131/161) were in those ≥65; there were none in those <5, 1 in those 5–17, 5 in those 18–44, and 24 in those 45–64. Conclusion: We found that the number of encounters per MAAGE episode increased with age and that outpatient and remote encounters are important settings for the initial clinical management of MAAGE in all ages. These data can help to better quantify the economic burden of AGE and guide appropriate delivery of healthcare services. Disclosures: All authors: No reported disclosures.